A proteção dos direitos da personalidade de migrantes e refugiados: uma análise do direito de família como garantidor face às medidas de cooperação e retirada compulsória do país - Sodré, Catarina Ribeiro (2024)
The research methodology is qualitative, bibliographical and documentary. This study is justified by its scientific relevance at national and international level, since it contributes to the examination of the legal personality rights of migrants and refugees associated with family law and family responsibility, observing the collection and analysis of doctrine, jurisprudence and legislation, from the perspective of Brazilian Civil Law and Comparative Law. In 2017, Brazil enacted the Migration Law (Law No. 13.445/2017), which was designed to implement new paradigms for the treatment of migrants and refugees in the country. In this context, the personality rights of migrants and refugees will be analysed, such as the right to freedom of movement and residence, citizenship and the right to establish a family. In this segment, it will be essential to verify the respect and viability of the family nucleus in cases involving co-operation measures and compulsory removal from the country under the Migration Law, as a way of providing a better understanding of the issue